Does Resident Trauma Exposure Affect Advanced Trauma Operative Management Course Experience?. Issue 3 (March 2016) - Kaban, Jody M.; Stone, Melvin E.; Dayama, Anand; Safadjou, Saman; Reddy, Srinivas H.; Simon, Ronald; Teperman, Sheldon
The Advanced Trauma Operative Management (ATOM) course is a simulation course adopted by the American College of Surgeons to teach operative management of primarily penetrating, traumatic injuries. Although it is clear that overall operative trauma exposure is decreasing, the educational benefit of ATOM for residents with different amounts of trauma exposure remains unclear. Our aim was to determine whether residents from trauma centers experienced less benefit from the ATOM course when compared with residents from nontrauma centers. We compared two groups of residents who take ATOM through our institutional course, those from trauma centers and those from nontrauma centers. ATOM pre- and postcourse evaluations of knowledge and self-efficacy were collected from October 2007 to June 2013. Overall residents from three institutions, two trauma centers (100 residents) and one nontrauma center (34 residents), were included in the study. All resident groups had statistically significant improvement in knowledge and self-efficacy after taking the ATOM course ( P < 0.0001). There was no statistically significant difference in improvement relative to each of the groups in the ATOM categories of knowledge and self-efficacy. Our data show that residents with different levels of trauma exposure had similar pre- and postcourse scores as well as improvement in the ATOM evaluations. As operative trauma continues to decrease the ATOM course shows benefit for all residents regardless of the depth of their clinical trauma exposure in surgical residency.